PRECONDITIONS OF MEGACITIES’ SUCCESSFUL DEVELOPMENT - A. Gaponenko; M. Savelyeva; A. Valetov (Управленческие науки)
In the unstable, rapidly changing globalized world of today the role of megacities in the global economy has become predominant. In view of this the purpose of the study is to identify the preconditions of the successful development of megacities. To achieve the goal the following tasks have been solved: designation of the key characteristics of megacities, singling out the key factors of their development, development of the guidelines of their competitiveness strengthening.Theoretical and methodological basis of the study are the provisions and conclusions of domestic and foreign scientists’ research into the development of cities. International statistics as well as the materials of the Federal State Statistics Service of the Russian Federation have been used. Information analysis and synthesis technique, as well as method of expert evaluations have been applied in the research.The preconditions of megacities’ successful development include diversification of their economies, deployment of innovation centers, carrying out research and development and experimental-design works, the formation of research institutions to develop new technologies, organization of international events, maintaining the transparency of national borders by national governments for talented professionals from other countries, the development of internal and external communications, management of migration and provision of citizens with affordable housing. The result of the selection of the key preconditions for megacities’ successful development is working out the guidelines for their development and for strengthening their competitiveness. Thus, to improve the image of Russia and Moscow there is a need to inform foreign business communities about the advantages of our country and its capital as business venues for theconstructive business dialogue having effective high-tech financial infrastructure, to provide for Moscow’sparticipation in the Forum of world financial centers, to organize one of these forums directly in Moscow.The results and conclusions of the article can be used in further research on the megacities’ development and strengthening their competitiveness.